Cover Image. (10th August 2021) - Wen, Qingqing; Wang, Kang; Hsu, Yi‐Cheng; Xu, Yan; Sun, Yi; Wu, Dan; Zhang, Yi
Abstract : The cover image is based on the Research Article Chemical exchange saturation transfer imaging for epilepsy secondary to tuberous sclerosis complex at 3 T: Optimization and analysis by Qingqing Wen et al., https://doi.org/10.1002/nbm.4563 .